Observation, hypothesis, introspection - Wiegner, Adam, 1889-1967 (Poznań studies in the philosophy of the sciences and the humanities, 2005)
Annotation "Adam Wiegner's work belongs to Polish analytical philosophy, but it falls outside of its main current, the Lvov-Warsaw School, which was influenced by Hume's ideas. Wiegner, influenced by neo-Kantianism, developed a non-Humean conception of "holistic empiricism," which anticipates some of the ideas of K.R. Popper and W.V.O. Quine. Some of his ideas remain original to this day. His main research interests included epistemology, philosophy of mind, philosophy of science especially philosophy of psychology, analytical history of philosophy, and interpretation of traditional logic in terms of mathematical logic."--Jacket